Combined local flap and antrostomy in recurrent oroantral fistula and chronic maxillary atelectasis: a case report - Bouthenet Franklin; Amroun Samy; Zwetyenga Narcisse (EDP Sciences, 2021)
Introduction: Chronic maxillary atelectasis refers to a persistent volume decrease of the maxillary sinus by inward bowing of its walls. When associated with hypoglobus or enophthalmos, some authors use the term "silent sinus syndrome". We aimed to report a case of accidental diagnosis of chronic maxillary atelectasis while investigating and treating a recurrent oroantral fistula. Observation: CT imaging showed a large bone defect and stage II chronic maxillary atelectasis. Closure of the oroantral fistula was performed with a combined surgical approach: functional endoscopic surgery and buccal fat pad flap. The follow up at 2 months showed no signs of recurrent oroantral fistula. Commentaries: Chronic maxillary atelectasis is separated into three stages, membranous deformity (stage I), bony deformity (stage II), and clinical deformity (stage III). The term silent sinus syndrome should be abandoned for stage III chronic maxillary atelectasis to allow for better collaboration between medical practitioners. Recurrent oroantral fistulas should be treated with a combined approach including endoscopic antrostomy and local flap. Conclusion: The association of functional endoscopic surgery and buccal fat pad flap were the key to success in this case allowing for oroantral fistula closure and treatment of chronic maxillary atelectasis.